Ammonium Activates Ouabain-Activated Signalling Pathway in Astrocytes: Therapeutic Potential of Ouabain Antagonist - Song, Dan; Du, Ting (Current Neuropharmacology, 2014)
The causal role of ammonium in hepatic encephalopathy was identified in 1930s. Astroglial cells are primary cellular elements of hepatic encephalopathy which conceptually, can be considered a toxic astrogliopathology. Previously we have reported that acute exposure to ammonium activated ouabain/Na,K-ATPase signalling pathway, which includes Src, EGF receptor, Raf, Ras, MEK and ERK1/2. Chronic incubation of astrocytes with ammonium increased production of endogenous ouabain-like compound. Ouabain antagonist canrenone abolished effects of ammonium on astrocytic swelling, ROS production, and upregulation of gene expression and function of TRPC1 and Cav1.2. However, ammonium induces multiple pathological modifications in astrocytes, and some of them may be not related to this signalling pathway. In this review, we focus on the effect of ammonium on ouabain/Na,K-ATPase signalling pathway and its involvement in ammonium-induced ROS production, cell swelling and aberration of Ca2+ signals in astrocytes. We also briefly discuss Na,K-ATPase, EGF receptor, endogenous ouabain and ouabain antagonist.
Keywords: Na